PENGARUH MOTIF TERHADAP KEPUASAN FOLLOWERS AKUN INSTAGRAM @SMBTELKOM - Rekha Karelina; Sylvie Nurfebiaraning (Jurnal Komunikasi dan Kajian Media, 2020)
Abstract: New media can become a forum for someone who wants to disseminate information just with one delivery  to all levels of society simultaneously. This new media is called social media. Dissemination of information through social media is carried out by the SMB Telkom National Admission, which uses Instagram with @smbtelkom account name. The aim of this study is to find out how much the influence of the motive has on the satisfaction of followers of @smbtelkom's Instagram account. In this study, quantitative research methods are used. The population in this study is the followers of @smbtelkom Instgram account. The sample amounted to 100 people using random sampling techniques. The results of this study are that there is a motive effect on satisfaction of Instagram @smbtelkom account followers by 63.9%. In the Motive variable, the most influential sub variable is Information Motive with a percentage of 84.6%. Likewise with the Satisfaction variable, the most influential sub variable is Information Satisfaction with a percentage of 84.0%.